Validation of an Extractive Spectrophotometric Method for Determining Lauric Acid in Virgin Coconut Oil - Raghav, Arvind; Rastogi, Vaibhav; Prabahar, Arulsamy Elphine (International Journal of Pharmaceutical Investigation, 2025)
Background An easy, quick, sensitive and precise extractive spectroscopic approach has been devised for the determination of lauric acid in pure form as well as present in virgin coconut oil. The approach is based on the formation of a brightly coloured ion-pair complex between the anionic drug (lauric acid) and cationic dye (methylene blue) in an alkaline solution. Materials and Methods This approach is stable and extracted into a chloroform layer (ion-pair complex). This complex is stable and can be extracted into a chloroform phase. All experimental conditions were optimized, and the maximum absorbance of the complex was observed at 653 nm in the visible spectrum, using chloroform as the reagent blank. To get the highest possible colour intensity, reaction conditions were modified. Results The study demonstrated that Beer's law is applicable within a conc. range of 1-8 µg/mL, with a correlation coefficient (r2), was found to be 0.9956. The approach was extensively validated following the guidelines set by the International Conference on Harmonization (ICH) and adhered to the criteria established by the U.S. Pharmacopoeia. It was successfully employed to analyze the target compound in pharmaceutical formulations, yielding satisfactory recovery rates. From this research, the limit of detection was 0.7002 µg/mL and the limit of quantification was 2.334 µg/mL. The method demonstrated reliable precision, with a Relative Standard Deviation (%RSD) below 2%, and an accuracy rate reflected in a recovery of 104.13%. Conclusion Based on the results, the proposed method is suitable for quality control and routine analysis of ionic drugs such as lauric acid (anionic drug) in combination with methylene blue (cationic dye).
Keywords: Lauric acid; Methylene blue; Extractive spectroscopy; Ion pair complex; Quantification; Validation